1993
DOI: 10.1063/1.465015
|View full text |Cite
|
Sign up to set email alerts
|

Fit of the potential energy surface for the reaction Ne+H2+→NeH++H using three different functional forms

Abstract: Articles you may be interested inCross sections and rate constants for OH + H2 reaction on three different potential energy surfaces for rovibrationally excited reagents J. Chem. Phys. 135, 194302 (2011); 10.1063/1.3660222 Predicting observables on different potential energy surfaces using feature sensitivity analysis: Application to the collinear H+H2 exchange reaction J. Chem. Phys. 97, 6240 (1992); 10.1063/1.463685 Distributed complex Gaussian basis sets: A useful function space for the solution of predisso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
4

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 23 publications
3
45
4
Order By: Relevance
“…The quantum calculations predict a very rapid increase of the proton transfer cross section at threshold, corresponding to curvature parameters ͓Eq. 3 Barring important shortcomings in the quantum scattering studies, this suggests that the potential energy surfaces derived for the H 2 + +He system are of significantly higher quality than the H 2 + +Ne surface provided by Pendergast and co-workers, 8 and that the improved accuracy of the surface significantly affects the dynamics calculations. Such low curvature parameters are indicative of longer-lived intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…The quantum calculations predict a very rapid increase of the proton transfer cross section at threshold, corresponding to curvature parameters ͓Eq. 3 Barring important shortcomings in the quantum scattering studies, this suggests that the potential energy surfaces derived for the H 2 + +He system are of significantly higher quality than the H 2 + +Ne surface provided by Pendergast and co-workers, 8 and that the improved accuracy of the surface significantly affects the dynamics calculations. Such low curvature parameters are indicative of longer-lived intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…16. Detailed information of the three different fits and the minimum energy paths is given in [125]. The differences in the fits are seen more clearly when these PESs are used in dynamics calculations: bound state calculations for the rovibrational levels of NeHt and its isotopomeres, quantum scattering studies of long lived resonances for the reaction Ne + Ht ~ NeH+ + H [426] and quasiclassical and approximate quantum mechanical (R-IOSA) studies of the intramolecular isotope effects in proton transfer: Ne + HD+ ~ NeH+ (NeD+) + D (H) [427].…”
Section: Comparison Of Different Fits In Some Test Casesmentioning
confidence: 99%
“…Reactions of Ne þ H þ 2 =Ne þ HD þ =Ne þ HT þ have been considered as typical ion-molecule reactions by some studies. In 1993, an accurate PES of the ground state of the NeH þ 2 reactive system was presented by Pendergast et al [1] using the coupled-electron approach, whereafter more studies have been conducted based on this PES. Kress et al [2] reported the state-tostate reaction probabilities for zero total angular momentum based on the bending-corrected rotating linear model using quantumdynamics calculations.…”
Section: Introductionmentioning
confidence: 99%